English Immersion Program in EFL Setting: A Modified Model, Implementation, and Effectiveness - Yusup Supriyono; Yuyus Saputra; Nita Sari Narulita Dewi (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2020)
This study reflects the best practice of the English immersion program designed for EFL learners.Â Through observation in the research site and interview with eight participants (two language managers and six language learners), the modified model is discovered as the guidelines in ruling the project in which curriculum, English proficiency, and language management are the main points. Besides, Informal learning becomes the hot issue of this study since the English zone facilitates English informal interaction between language partners and learners which enhances English learning experiences effectively and motivates them to use English. The finding also reported that English immersion program emerges learning community, personal qualities development, English language acquisition, and self-efficacy, language awareness and language exposure The study may contribute to the body of knowledge in second language acquisition and recommend schools or universities and other related institutions to implement English immersion program as the alternative solution for English language learning in non-native speaking countries.